The child-youths powerlifting in sports schools system - Stetsenko Anatolij Ivanovich (Kharkov National Pedagogical University, 2011)
The article provides data on the functioning of child-youths sports schools in current condition. Were studied the characteristics of powerlifting distribution in system Ukrainian child-youths sports schools and made a comparative analysis of representation in national competitions. It was established, that are taking part in these competitions not all powerlifting branches of child-youths sports schools. Ways of further development of powerlifting in the system child-youths sports schools in Ukraine are presented. Proposed a unified form of control over their activities in conjunction with the National Federation of Ukraine Powerlifting for increase the efficiency of the powerlifting branches of child-youths sports schools.